Circulating exosomal miRNAs in cardiovascular disease pathogenesis: New emerging hopes. Issue 12 (5th July 2019) - Aghabozorgi, Amirsaeed S.; Ahangari, Najmeh; Eftekhaari, Tasnim E.; Torbati, Paria N.; Bahiraee, Alireza; Ebrahimi, Reyhane; Pasdar, Alireza
Abstract: Cardiovascular diseases (CVDs) are one of the leading causes of morbidity and mortality. Standard therapies have failed to significantly increase patients' survival. Moreover, the majority of conventional screening procedures are ineffective for the diagnosis of CVDs at early stages. Accumulating evidence suggests that numerous cell types release a class of nano‐sized vesicles named exosomes into the extracellular space. Exosomes are widely distributed in various body fluids and contain a number of diverse biomolecules such as proteins, lipids, and both mRNA and noncoding RNAs which reflect host‐cell molecular architecture. MicroRNAs (miRNAs), which can be found in exosomes, could be taken up by both neighboring and distal cells. Not only has recent evidence indicated the regulatory role of exosomal miRNAs in the pathogenesis of CVD, but it has also been shown that differential expression of exosomal miRNAs in CVDs has made them promising biomarkers for early detection of CVDs. Owing to these remarkable features, exosomal miRNAs have emerged as hot spots in research. This review summarizes the role of exosomal miRNAs in the pathogenesis of CVDs and discusses their potential application in the clinical setting as both therapeutic and diagnostic tools. Abstract : Cardiovascular diseases (CVDs) are one of the leading causes of morbidity and mortality. MicroRNAs (miRNAs), which can be found in exosomes, could be taken up by both neighboring and distal cells. Exosomal miRNAs have emerged as hot spots in research.